2013
DOI: 10.1371/journal.pone.0067473
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Developmental Abnormalities in a Mouse with Systemic Pyruvate Dehydrogenase Deficiency

Abstract: Pyruvate dehydrogenase (PDH) complex (PDC) deficiency is an inborn error of pyruvate metabolism causing a variety of neurologic manifestations. Systematic analyses of development of affected brain structures and the cellular processes responsible for their impairment have not been performed due to the lack of an animal model for PDC deficiency. METHODS: In the present study we investigated a murine model of systemic PDC deficiency by interrupting the X-linked Pdha1 gene encoding the α subunit of PDH to study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 42 publications
5
20
0
Order By: Relevance
“…Also (2), mice deficient for a lactate transporter in Schwann cells showed thinning of myelin in sensory fibers associated with a reduced fatty acid and sphingosine synthesis [116]. In addition (3), myelin defects occurred with pyruvate dehydrogenase deficiency, an enzyme required for the synthesis of acetyl-coA from glycolytic sources [117,118]. However, a recent study reported that myelination is normal in animals with ablated pyruvate dehydrogenase in myelinating cells, indicating that oligodendrocytes and Schwann cells metabolism do not rely essential on glycolytic sources for the generation of acetyl-CoA [119].…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
“…Also (2), mice deficient for a lactate transporter in Schwann cells showed thinning of myelin in sensory fibers associated with a reduced fatty acid and sphingosine synthesis [116]. In addition (3), myelin defects occurred with pyruvate dehydrogenase deficiency, an enzyme required for the synthesis of acetyl-coA from glycolytic sources [117,118]. However, a recent study reported that myelination is normal in animals with ablated pyruvate dehydrogenase in myelinating cells, indicating that oligodendrocytes and Schwann cells metabolism do not rely essential on glycolytic sources for the generation of acetyl-CoA [119].…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
“…These disorders include PDC deficiency, lipoamide dehydrogenase deficiency, or Amish lethal microcephaly syndromes (3,11,13). It is also worth noting that complete KO mouse models for Pdha1, Dld, Slc25a19, as well as for E4f1, all show severe developmental defects and lethality during early embryonic development (4,22,(37)(38)(39). This finding raises interesting questions about the importance of the E4F1-controlled PDH-program during embryogenesis and beyond, about the poorly characterized metabolic rewiring of the pyruvate pathway that may occur during development.…”
Section: Muscular Defects Of E4f1 Ko(acta) Mice Are Rescued Upon Pharmentioning
confidence: 99%
“… PDHC E1 α null mutation in mice Low PDC activity, reduced litter size All males die & 50% females survive after only brain‐targeted mutation, females show ↓neuronal density & neuropil fibers, abnormal neuronal localization in the gray matter, ↓lipid synthesis & irregular myelination, adult females have neurological deficits PDHC E1 α knockdown in striatum & SN in rats abnormal amphetamine‐induced rotation Systemic deletion of exon 8 from PDHC E1 α ↓ brain weight, de novo lipid synthesis, ↓ proliferation, differentiation and migration of newly generated neuronal precursor cells in cerebellum, impaired dendritic development of Purkinje cells ex vivo Impaired acoustic startle reflex E2 impairment in zebrafish Ketogenic diet reversed abnormal vision, lactic acidosis & lethargy …”
Section: Metabolic Errors In Organic Moleculesmentioning
confidence: 99%
“…Knockdown of the PDHC E1 α subunit via the delivery of siRNAs into striatum and substantia nigra of rats led to abnormal amphetamine‐induced rotation indicating degenerative changes in the nigrostriatal system . A recent investigation of a systemic deletion of exon 8 from PDHC E1 α subunit in mice showed general decrease in brain weight, de novo lipid synthesis, reduced proliferation, differentiation, and migration of newly generated neuronal precursor cells in prenatal and postnatal periods in cerebellum and impaired dendritic development of Purkinje cells . The locomotor activity was normal in these mice; however, they had impaired acoustic startle reflex indicating mild motor abnormalities.…”
Section: Metabolic Errors In Organellesmentioning
confidence: 99%